Effective connectivity differs between focal cortical dysplasia types I and II. (20th September 2021) - Shahabi, Hossein; Taylor, Kenneth; Hirfanoglu, Tugba; Koneru, Shreekanth; Bingaman, William; Kobayashi, Katsuya; Kobayashi, Masako; Joshi, Anand; Leahy, Richard M.; Mosher, John C.; Bulacio, Juan; Nair, Dileep
Abstract: Objective: To determine whether brain connectivity differs between focal cortical dysplasia (FCD) types I and II. Methods: We compared cortico‐cortical evoked potentials (CCEPs) as measures of effective brain connectivity in 25 FCD patients with drug‐resistant focal epilepsy who underwent intracranial evaluation with stereo‐electroencephalography (SEEG). We analyzed the amplitude and latency of CCEP responses following ictal‐onset single‐pulse electrical stimulation (iSPES). Results: In comparison to FCD type II, patients with type I demonstrated significantly larger responses in the electrodes near the ictal‐onset zone (<50 mm). These findings persisted when controlling for the location of the epileptogenic zone, as noted in patients with temporal lobe epilepsies, as well as controlling for seizure type, as noted in patients with focal to bilateral tonic‐clonic seizures (FBTCS). In type II, the root mean square (RMS) of CCEP responses dropped substantially from the early segment (10–60 ms) to the middle and late segments (60–600 ms). The middle and late CCEP latency segments showed the largest differences between FCD types I and II. Significance: Focal cortical dysplasia type I may have a greater degree of cortical hyperexcitability as compared with FCD type II. In addition, FCD type II displays a more restrictive area of hyperexcitability in both temporal and spatial domains. In patients with FBTCS and type I FCD, the increased amplitudes of RMS in the middle and late CCEP periods appear consistent with the cortico‐thalamo‐cortical network involvement of FBTCS. The notable differences in degree and extent of hyperexcitability may contribute to the different postsurgical seizure outcomes noted between these two pathological substrates.